Calvarial Suture-Derived Stem Cells and Their Contribution to Cranial Bone Repair - Doro, Daniel H.; Grigoriadis, Agamemnon E.; Liu, Karen J. (Frontiers in Physiology, 2017)
In addition to the natural turnover during life, the bones in the skeleton possess the ability to self-repair in response to injury or disease-related bone loss. Based on studies of bone defect models, both processes are largely supported by resident stem cells. In the long bones, the source of skeletal stem cells has been widely investigated over the years, where the major stem cell population is thought to reside in the perivascular niche of the bone marrow. In contrast, we have very limited knowledge about the stem cells contributing to the repair of calvarial bones. In fact, until recently, the presence of specific stem cells in adult craniofacial bones was uncertain. These flat bones are mainly formed via intramembranous rather than endochondral ossification and thus contain minimal bone marrow space. It has been previously proposed that the overlying periosteum and underlying dura mater provide osteoprogenitors for calvarial bone repair. Nonetheless, recent studies have identified a major stem cell population within the suture mesenchyme with multiple differentiation abilities and intrinsic reparative potential. Here we provide an updated review of calvarial stem cells and potential mechanisms of regulation in the context of skull injury repair.